Assessing the influence of legal constraints on the integration of renewable energy technologies in polygeneration systems for buildings. (October 2021) - Pina, Eduardo A.; Lozano, Miguel A.; Serra, Luis M.
Abstract: Hybrid polygeneration systems offer a great opportunity to meet growing energy demands with cost efficiency and environmental benefits. The identification of the optimal solution (configuration and operational strategy) is strongly affected by the relationship between the system and its surroundings. Previous studies have analyzed the influence of boundary conditions on the synthesis of polygeneration systems for buildings. However, local regulations are often disregarded or oversimplified in those studies. Therefore, this paper aims to evaluate the influence of legal conditions on the integration of renewable energy technologies in polygeneration systems for buildings. A comprehensive synthesis model is developed, including different types of legal conditions, such as power exchange modalities, subsidies/surcharges on energy prices and investment costs, and total ban on fossil fuels. Then, the model is applied to the case study of a Brazilian hospital. The current Brazilian net metering scheme is implemented. Results show that natural gas cogeneration is an attractive solution to cover the hospital's energy demands with or without the possibility of selling/exporting electricity. Also, the Brazilian net metering scheme, by itself, is not enough to ensure renewable energy deployment. An in-depth discussion about the conditions that would promote renewable energy integration is reported and recommendations are made on how current policies can be improved, including the need to explicitly address renewable technologies, the application of minimum renewable fractions, and the role of renewable heat/cooling. While the case study considers the specific circumstances in Brazil, it provides insights that can be extended to other countries or applications. Highlights: Synthesis model of hybrid renewable polygeneration systems for buildings. Influence of legal constraints on the integration of renewable energy technologies. Power exchange modalities, subsidies/surcharges, and fossil fuel ban are considered. Technical, economic, and environmental analysis of a Brazilian hospital case study. The Brazilian net metering scheme did not promote renewable energy technologies.